English Language Training in the Ukrainian Military Academies: Problems for Teachers and Curriculum Developers - LAGODYNSKYI, Oleksandr (Journal of Education, Technology and Computer Science, 2013)
The article identifies major problems the teachers and curriculum developers have with the English Language Training in the Ukrainian military academies. It gives recommendations on how to solve them in order to improve language interoperability of the Ukrainian armed forces with the foreign military.